MHD Equations with Regularity in One Direction
MHD Equations with Regularity in One Direction
We consider the 3D MHD equations and prove that if one directional derivative of the fluid velocity, say, <mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" id="M1"><mml:msub><mml:mrow><mml:mo>∂</mml:mo></mml:mrow><mml:mrow><mml:mn>3</mml:mn></mml:mrow></mml:msub><mml:mi mathvariant="bold-italic">u</mml:mi><mml:mo>∈</mml:mo><mml:msup><mml:mrow><mml:mi>L</mml:mi></mml:mrow><mml:mrow><mml:mi>p</mml:mi></mml:mrow></mml:msup><mml:mfenced separators="|"><mml:mrow><mml:mn>0</mml:mn><mml:mo>,</mml:mo><mml:mi> </mml:mi><mml:mi>T</mml:mi><mml:mo>;</mml:mo><mml:msup><mml:mrow><mml:mi>L</mml:mi></mml:mrow><mml:mrow><mml:mi>q</mml:mi></mml:mrow></mml:msup><mml:mfenced separators="|"><mml:mrow><mml:msup><mml:mrow><mml:mi mathvariant="bold-italic">R</mml:mi></mml:mrow><mml:mrow><mml:mn>3</mml:mn></mml:mrow></mml:msup></mml:mrow></mml:mfenced></mml:mrow></mml:mfenced></mml:math>, with <mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" id="M2"><mml:mn>2</mml:mn><mml:mo>/</mml:mo><mml:mi>p</mml:mi><mml:mi> </mml:mi><mml:mo>+</mml:mo><mml:mi> </mml:mi><mml:mn>3</mml:mn><mml:mo>/</mml:mo><mml:mi>q</mml:mi><mml:mi> </mml:mi><mml:mo>=</mml:mo><mml:mi> </mml:mi><mml:mi>γ</mml:mi><mml:mi> </mml:mi><mml:mo>∈</mml:mo><mml:mi> </mml:mi><mml:mo stretchy="false">[</mml:mo><mml:mn>1,3</mml:mn><mml:mo>/</mml:mo><mml:mn>2</mml:mn><mml:mo stretchy="false">)</mml:mo></mml:math>, <mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" id="M3"><mml:mn>3</mml:mn><mml:mo>/</mml:mo><mml:mi>γ</mml:mi><mml:mi> </mml:mi><mml:mo>≤</mml:mo><mml:mi> </mml:mi><mml:mi>q</mml:mi><mml:mi> </mml:mi><mml:mo>≤</mml:mo><mml:mi> </mml:mi><mml:mn>1</mml:mn><mml:mo>/</mml:mo><mml:mo stretchy="false">(</mml:mo><mml:mi>γ</mml:mi><mml:mi> </mml:mi><mml:mo>-</mml:mo><mml:mi> </mml:mi><mml:mn>1</mml:mn><mml:mo stretchy="false">)</mml:mo></mml:math>, then …